Chemical speciation and bioavailability of cadmium and lead in the gray calcium soil. Issue 1 (1st January 2019) - Yang, Yiming; Zeng, Liang; Chen, Lihua
ABSTRACT: A pot experiment was conducted to study chemical speciations and bioavailability of cadmium (Cd) and lead (Pb) in the gray calcium soil from northwestern China, and accumulation and translocation of Cd and Pb in wheat ( Triticum aestivum L .) grown on the soil was also studied. The results showed that significant changes of Cd and Pb fractions in the soil and Cd and Pb concentrations in the wheat were observed with increasing soil Cd and Pb concentrations, and both Cd and Pb in exchangebale fraction in the soil made the greatest contribution to the accumulation of Cd and Pb in the wheat. Higher bio-concentration factors (BCFs) and translocation factors (TFs) for Cd and lower BCFs and TFs for Pb were observed in the wheat, respectively, and Cd had much higher accumulation than Pb in the edible parts of the wheat. Therefore, Cd has higher risk than Pb when people eat the wheat.